Estimation of Stature from Head Circumference in Bangladeshi Santal Female Population: A Correlational Analysis - Talukder, Moumita; Das, Ripon Kumar; Basu, Jayasree; Afroze, Sadia Nure; Banu, Laila Anjuman; Khatun, Rokeya (Bangladesh Journal of Anatomy, 2018)
Context: Craniofacial anthropometry is an important stem of anthropometry in which the dimensions of the head and face are measured. Stature being one of the criteria of personal identification has a definite and proportional biological relationship with each and every part of the human body eg. head, face, trunk and extremities. The Santal community being one of the major tribes of Bangladesh, there are few recorded data in the literature on the craniofacial anthropometry of the Santal female population. The present study was designed to document the standard normal craniofacial measurements and stature of this tribal population and also to determine whether there is any correlation between the measured value of the stature and the physically measured cranial variable. Methods: The study was cross-sectional and descriptive type with some analytical components and was conducted on 100 Santal females. The study was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, between July 2012 and December 2013. The head circumference was measured by using a flexible measuring tape. The stature was taken by using a hard board and steel tape. Results: The head circumference showed significant positive correlation with stature. No significant difference was found between the “measured” and “estimated” stature for head circumference. Bangladesh Journal of Anatomy January 2018, Vol. 16, No. 1, pp. 3-8